Prognostic Impact of Multiple Lymphocyte-Based Inflammatory Indices in Acute Coronary Syndrome Patients - Li, Qiuxuan; Ma, Xiaoteng; Shao, Qiaoyu; Yang, Zhiqiang; Wang, Yufei; Gao, Fei; Zhou, Yujie; Yang, Lixia; Wang, Zhijian (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The aim of this study was to evaluate the prognostic values of 5 lymphocyte-based inflammatory indices (platelet-lymphocyte ratio [PLR], neutrophil-lymphocyte ratio [NLR], monocyte-lymphocyte ratio [MLR], systemic inflammatory reaction index [SII], and systemic inflammatory response index [SIRI]) in patients with acute coronary syndrome (ACS). Methods: A total of 1701 ACS patients who underwent percutaneous coronary intervention (PCI) were included in this study and followed up for major adverse cardiovascular events (MACE) including all-cause death, non-fatal ischemic stroke, and non-fatal myocardial infarction. The five indices were stratified by the optimal cutoff value for comparison. The association between each of lymphocyte-based inflammatory indices and MACE was assessed by the Cox proportional hazards regression analysis. Results: During the median follow-up of 30 months, 107 (6.3%) MACE were identified. The multivariate COX analysis showed that all five indices were independent predictors of MACE and SIRI seemingly performed best (HR, 3.847; 95% CI [2.623-5.641]; P < 0.001; C-statistic 0.794 [0.731-0.856]). The addition of NLR, MLR, SII, or SIRI to the GRACE risk score, especially SIRI (C-statistic 0.699 [0.646-0.753], P < 0.001; NRI 0.311 [0.209-0.407], P < 0.001; IDI 0.024 [0.010-0.046], P < 0.001), outperformed the GRACE risk score alone in the risk predictive performance. Conclusion: Lymphocyte-based inflammatory indices were significantly and independently associated with MACE in ACS patients who underwent PCI. SIRI seemed to be better than the other four indices in predicting MACE, and the combination of SIRI with the GRACE risk score could predict MACE more accurately.